Modeling and simulation of a gas detecting device for providing safety; and reducing the risk of accidents due to gas explosion or fire - Khan, Rafsan; Khan, Mashfiqul Islam; Soha, Anika Bushra; Zayed, Abdullah Al (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.